Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1103/physrevb.78.054517
|View full text |Cite
|
Sign up to set email alerts
|

Josephson modulation of the critical current inYBa2Cu3O7δfilms

Abstract: Assuming that the boundary planes in YBa 2 Cu 3 O 7−␦ can show a Josephson behavior, we establish the conditions required in epitaxial thin films to observe the modulation of the critical current by an applied magnetic field, as well as the possible forms of the modulated current. We report measurements carried out on two YBa 2 Cu 3 O 7−␦ films in the near vicinity of the critical temperature that show a partial modulation of their critical current. The comparison of the measured critical current changes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…3. Bernstein et al 40 suggested that planar defects split up in structures that locally behave like Josephson weak links or superconducting-quantum-interference-device ͑SQUID͒-like structures. Since along the whole length of the APB there are all kind of defect structures expected, it is difficult to make an exact description.…”
Section: Discussionmentioning
confidence: 99%
“…3. Bernstein et al 40 suggested that planar defects split up in structures that locally behave like Josephson weak links or superconducting-quantum-interference-device ͑SQUID͒-like structures. Since along the whole length of the APB there are all kind of defect structures expected, it is difficult to make an exact description.…”
Section: Discussionmentioning
confidence: 99%
“…The tunneling currents cannot flow across the boundary planes at the locations where, due to defects, the separation between both sides is large with respect to the coherence length. We have suggested that this results in the splitting of the boundary planes into rows of Josephson weak links [11,12] and established that ) T ( J S cr , for a YBCO film whose boundary planes include Z rows of Josephson weak links with the same T c , takes the form…”
Section: Determination Of the T C Profilesmentioning
confidence: 99%